Effect of concentration of Ce(NO3)3 · 6H2O and temperature on the corrosion resistance of Al2O3/cerium oxide composite films on 1060 Al alloy. Issue 7 (24th January 2019) - Li, Zeyuan; Ying, Lixia; Jin, Qiu; Wang, Guixiang; Chen, Shixing; Gao, Gang
Abstract : In this paper, Al2 O3 /cerium oxide composite films were prepared on the surface of aluminum by anodic oxidation and chemical solution deposition. The aluminum was firstly anodized in sulfuric acid, then treated with different concentrations of Ce(NO3 )3  · 6H2 O solution at different temperatures. X‐ray diffraction (XRD), energy dispersive spectrometer (EDS), scanning electron microscope (SEM), electrochemical impedance spectroscopy (EIS), and electrochemical polarization tests were used to characterize the properties of the composite films. The results indicate that the Al2 O3 /cerium oxide composite films successfully form on 1060 Al alloy, and the best condition of film‐forming is 2 g/L Ce(NO3 )3  · 6H2 O and 50 °C. Al2 O3 /cerium oxide composite film under this condition has a uniform, smooth, and pyknotic surface topography and optimal corrosion resistance. The corrosion density at that time is 1.106 × 10 −6  A/cm 2 and the corrosion potential is −0.458 V. Abstract : Al2 O3 /cerium oxide composite film was successfully prepared on Al surface by anodic oxidation and chemical solution deposition in the electrolyte containing 2 g/L Ce(NO3 )3  · 6H2 O and 20 ml/L H2 O2 for 50 °C at 30 min. The composite film has uniform, smooth, and pyknotic surface topography and optimal corrosion resistance. The corrosion current density is 1.106 × 10 −6  A/cm 2 and the corrosion potential is −0.458 V.